Industrial Applications of Reactive Distillation: Recent Trends - Hiwale, Rameshwar S; Bhate, Nitin V; Mahajan, Yogesh S; Mahajani, Sanjay M. (International journal of chemical reactor engineering, 2004)
Last few years have seen a dramatic rise in the number of applications of reactive distillation (RD). This useful technology is now being applied for any scale of operation- from manufacture of fine chemicals to that of bulk chemicals. This article reviews the very recent applications and serves as a supplement for the exhaustive review on this subject by Sharma and Mahajani (2003). It not only furnishes the information on the ongoing research in the existing applications but also elaborates the newly discovered applications such as manufacture of phenol, linear alkyl benzene, carbonates, chlorosilane derivatives and chiral chemicals. Multiple reactions in RD, failure of RD in some cases and new RD configurations to increase the overall yields are some of the additional aspects being covered.